Reduced Sensitivity of Older Adults to Affective Mismatches - Yang Jiang; Victoria Vagnini; Jessica Clark; Qin Zhang (The Scientific World Journal)
The present study investigated age-related differences in emotional processing by using a paradigm of affective priming. Eighteen, right-handed, younger (mean age 22) and 15 older (mean age 68) subjects pressed buttons to indicate pleasantness of target words. The valence of each prime-target pair was congruent (e.g., win-love), incongruent (e.g., love-loss), or neutral (time-flower). Two sets of 720 prime-target pairs used either affective words or pictures as primes, and affect words as targets. We included well-matched positive and negative valence pairs in all congruent, neutral, and incongruent conditions, and controlled for possible contamination by semantic meaning, word frequency, and repetition effects. The response time (RT) results revealed that young participants responded faster to the targets in affectively congruent conditions than in incongruent conditions. In older participants, the responses to target words were indifferent to all valence congruency conditions. The age effect in affective priming largely reflects reduced sensitivity to affective mismatches among older adults. Intriguingly, emotional Stroop effect and some perceptual priming have been linked to increased interferences and mismatches in older adults. The age-related changes in affective, perceptual, and semantic processes are discussed.